Gingival and Teeth Display in Relation to Gender at Rest and Smiling Position Among the Undergraduate Students of Dhulikhel Hospital – A Cross Sectional Study - Basnyat, S KC; Dhyako, R; Suwal, P; Baidya, S; Bhochhibhoya, R; Basnet, S (Journal of Nepalese Prosthodontic Society, 2024)
Introduction: The smile is one of the most important facial expressions for expressing joy, pleasure, mood and gratefulness. In the present research, we aim to investigate the maxillary anterior teeth and associated gingival display among the genders when the lips are at rest and during smiling. Methods: A total of 284 undergraduate students of Kathmandu University School of Medical Sciences were selected as participants. Crown length, displayed portions of anterior teeth, and associated gingivae at rest and during smiling were measured using digital vernier calliper by two observers on the same patient. Student t test and ANOVA will be used comparison between amount of teeth displayed and gingival display at rest and during smiling. Statistical evaluation will be done using the statistical package for social sciences (SPSS 20.0), the level of significance set at p-value <0.05. Results: The mean value of crown length in male for all maxillary anterior teeth are slightly higher than the corresponding length in female. There was no significant gender difference in the display of maxillary central incisors were recorded (p>0.001). There was a significant difference in tooth and gingival portion display with lips at rest between male and female(p<0.001). Conclusions: This study at Dhulikhel Hospital found that males display more maxillary right lateral incisors at rest, while females show more maxillary left and right central incisors and more maxillary anterior teeth while smiling.These gender-specific differences are crucial for optimizing dental aesthetics and warrant further research.